Development of Computerized Recording Channel of Lung Sound - Al-Naggar, Noman Qaid Abdullah (EJournal Publishing, 2012)
Lung sound (LS) records are first stage of studying breathing diseases and indicate the lung function performance. This paper gives a developing method that records LS using a computerized channel. It discusses the chosen components of this channel that reduce noises. Other purpose of this paper is to provide detailed discussions of the issues concerning digitization and sampling frequency of LS records. The method of recording LS includes two trends: developed hardware and created software. Hardware part ends in analog-digital input of sound card with ADC 16 bits. Software includes displaying LS using created program by Graphical User Interface (GUI) MATLAB. It provides LS record in wave data with 44.1 kHz sampling frequency and converts it to 11.025 kHz sampling frequency for future analysis. The developed computerized recoding channel of lung sound (CRCLS) achieves sensing, capturing, recording, displaying, converting and storing LS records.